2022
DOI: 10.1097/md.0000000000030759
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase/albumin ratio as a prognostic factor in severe acute respiratory distress syndrome cases associated with COVID-19

Abstract: Background: Patients with severe acute respiratory distress syndrome (ARDS) have high mortality rates; therefore, new biomarkers are necessary to predict the prognosis in the early stages. Serum lactate dehydrogenase (LDH) level is a specific marker of lung damage, but it is not sensitive because it is affected by several factors. This study aimed to determine whether the LDH/albumin ratio could be used as a prognostic biomarker in patients with severe ARDS due to COVID 19.Methods: Tertiary intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Thus, the index [Urea] × [MDA]/(BChEb × [ALB]) can claim to take a place among the most promising indices proposed to date, among which there is none that includes the activity of BChE and at the same time demonstrates such striking differences at the stage of admission to the clinic between survivors and those who died during treatment from COVID-19. At the same time, it should be mentioned that most of the proposed indices include albumin in the denominator: LDH/[ALB], [Lact]/[ALB], [Fibr]/[ALB], [Urea]/[ALB], and [CRP]/[ALB] [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Importantly, correlation analysis independent of age and concomitant pathology showed that the ratio of [CRP]/[ALB] negatively correlates with oxygen saturation (SO 2 ), spirometric indices (FEV1, forced expiratory volume in the first second, and FVC, forced volume capacity) and lung diffusion values (DLCO, carbon monoxide diffusion capacity) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the index [Urea] × [MDA]/(BChEb × [ALB]) can claim to take a place among the most promising indices proposed to date, among which there is none that includes the activity of BChE and at the same time demonstrates such striking differences at the stage of admission to the clinic between survivors and those who died during treatment from COVID-19. At the same time, it should be mentioned that most of the proposed indices include albumin in the denominator: LDH/[ALB], [Lact]/[ALB], [Fibr]/[ALB], [Urea]/[ALB], and [CRP]/[ALB] [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Importantly, correlation analysis independent of age and concomitant pathology showed that the ratio of [CRP]/[ALB] negatively correlates with oxygen saturation (SO 2 ), spirometric indices (FEV1, forced expiratory volume in the first second, and FVC, forced volume capacity) and lung diffusion values (DLCO, carbon monoxide diffusion capacity) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…[Urea]/[ALB], and [CRP]/[ALB] [42][43][44][45][46][47][48][49][50][51]. Importantly, correlation analysis independent of age and concomitant pathology showed that the ratio of [CRP]/[ALB] negatively correlates with oxygen saturation (SO 2 ), spirometric indices (FEV1, forced expiratory volume in the first second, and FVC, forced volume capacity) and lung diffusion values (DLCO, carbon monoxide diffusion capacity) [52].…”
Section: Comparative Analysis Of Esterase Status Of Survivors and Dec...mentioning
confidence: 99%
“…One previous study showed that LAR was an independent risk factor for mortality for the patients with ARDS due to COVID-19 ( 12 ), but the study only revealed the relationship between LAR and the death outcome, which may not reflect the overall dynamics of the patient’s condition.…”
Section: Introductionmentioning
confidence: 91%
“…[Lactate]/[ALB], [Fibrinogen]/[ALB], [Urea]/[ALB], and [CRP]/[ALB] [24][25][26][27][28][29][30][31][32][33]. It is important to note that correlation analysis, regardless of age and comorbidity, showed that the [CRP]/[ALB] ratio negatively correlates with oxygen saturation (SO 2 ), spirometric parameters (FEV1, forced expiratory volume in the first second; FVC, forced vital capacity), and lung diffusion values (DLCO, diffusion lung capacity for carbon monoxide) [34].…”
Section: Introductionmentioning
confidence: 99%